Consumptive Behavior in Early Adult NCTzen (Descriptive Study: NCTzen Fans in Tangerang) - Satwika, Yohana Wuri; Hafid, Bella Indi Rahmawati; Wati, Dewi Fatma (Procedia of Social Sciences and Humanities, 2024)
The spread of K-Pop is taking place rapidly around the world including in Indonesia. This has become a trend for young people, which can lead to consumptive behavior to buy things related to the idols they like. This study aims to determine the description of consumptive behavior in early adult NCTzen in Tangerang. The research method used in this study is the descriptive quantitative method. The subjects in the study amounted to 272 people with the criteria of NCT fans or NCTzen, aged 18-25 years, domiciled in Tangerang. The data collection technique used a questionnaire containing a consumptive behavior scale. The findings showed that consumptive behavior in early adult NCTzen in Tangerang showed a moderate category.